Whipple's disease unmasked by TNF inhibitor therapy for treatment of seronegative rheumatoid arthritis. Issue 7 (21st July 2022) - Mohammed, Fahad; Kurtom, Muhannad; Brant, Andrew; Sampath, Rahul
Abstract : We report a patient with seronegative rheumatoid arthritis diagnosed with Whipple's disease following treatment of tumour necrosis factor inhibitor (TNFI) therapy. Whipple's disease should be considered in patients with seronegative rheumatoid arthritis and other unexplained multisystem illness. The TNFI therapy and immunosuppressive therapies can unmask latent Whipple's disease.